1995
DOI: 10.1111/j.1432-1033.1995.347_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of Thioredoxin: 3′‐Phospho‐adenylylsulfate Reductase Investigated by Site‐Directed Mutagenesis

Abstract: Properties of purified recombinant adenosine 3'-phosphate 5'-phosphosulfate (PAdoPS) reductase from Escherichia coli were investigated. The Michaelis constants for reduced thioredoxin and PAdoPS are 23 pM and 10 pM, respectively; the enzyme has a V,,,,,, of 94-99 pmol min.. mg and a molecular activity/catalytically active dimer of 95 s-'. Adenosine 3',5'-bisphosphate (PAdoP) inhibits competetively ( K , 4 pM) with respect to PAdoPS; adenosine 2',5'-bisphosphate and sulfite are not inhibitory. Alkylation by SH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 26 publications
3
84
0
Order By: Relevance
“…This result first confirmed that C245 is the essential cysteine for MET16 interaction with TRXs (47). Second, this experiment demonstrated that the CY306 strain is a functional and reliable tool to discriminate cysteines targeted by TRXs in vivo.…”
Section: Cy306 Trx1⌬ Trx2⌬ Yeast Strain As a Tool To Reveal Essentialsupporting
confidence: 71%
See 1 more Smart Citation
“…This result first confirmed that C245 is the essential cysteine for MET16 interaction with TRXs (47). Second, this experiment demonstrated that the CY306 strain is a functional and reliable tool to discriminate cysteines targeted by TRXs in vivo.…”
Section: Cy306 Trx1⌬ Trx2⌬ Yeast Strain As a Tool To Reveal Essentialsupporting
confidence: 71%
“…We finally investigated the ability of the CY306 strain to reveal critical residues such as cysteines involved in TRX interaction with its target. We took as an example the MET16 enzyme that contains two cysteine residues: C112, which does not possess any catalytic activity (46), and C245 in the consensus sequence KxECG(L͞I)H, which is required for MET16 activity (47). Before this work, the identity of the cysteine residue targeted by TRX in MET16 was unknown.…”
Section: Cy306 Trx1⌬ Trx2⌬ Yeast Strain As a Tool To Reveal Essentialmentioning
confidence: 99%
“…All of these proteins are characterized by a highly conserved (KRT)ECG(LI)H motif ( Fig. 1) containing a catalytically active Cys residue (32,33). In addition, a number of related proteins of unknown function were found in several archaebacteria, including Methanococcus jannaschii, Pyrococcus horikoshii, and Pyrococcus abyssii.…”
Section: Evolutionary Relationships Of Aps and Paps Reductase-tomentioning
confidence: 99%
“…As expected, all mutants were auxotrophic for cysteine (Table 2); however, they displayed WT phenotypes on Congo red and calcofluor plates, with the partial exception of the cysQ mutant, showing some fluorescence on calcofluor medium (Fig. 2a) carrying either a WT cysH gene or a mutant allele, in which two codons encoding C-terminal amino acids identified as the redox-active centre of the enzyme (Berendt et al, 1995) had been substituted to obtain two alanine residues (pT7cysH wt and pT7cysH mut , respectively). Production of both the WT and mutated CysH proteins from the pT7-7 plasmid derivatives was clearly detectable on SDS-PAGE (Fig.…”
Section: Inactivation Of the Cysh Gene Affects The Production Of Extrmentioning
confidence: 99%
“…For expression of WT CysH protein, the corresponding gene was amplified by PCR from the E. coli MG1655 chromosome using primers cysH_NdeI_for and cysH_PstI_rev, and the resulting product was cloned into pT7-7 vector using the NdeI/ PstI restriction sites. The pT7cysH mut plasmid, carrying a mutant cysH allele encoding a protein with a non-functional redox-active centre (Berendt et al, 1995), was constructed by amplifying the cysH gene using primers cysH_NdeI_for and cysH_mut_PstI_rev, resulting in the following substitutions: TAG at nt 715, GAC at nt 716, CAG at nt 724, AAC at nt 725. The four mutations resulted in substitution of both Cys240 and His243 to alanine residues (ECGLHAEAGLA).…”
mentioning
confidence: 99%